1983
DOI: 10.1007/bf00607097
|View full text |Cite
|
Sign up to set email alerts
|

Steady state disposition of chloroquine in patients with rheumatoid disease

Abstract: The steady state disposition of chloroquine and its major metabolites, monodesethyl and bidesethyl chloroquine, were determined in 6 patients on long-term treatment for rheumatic disease with 99-155 mg base/day. The total body clearance of chloroquine was 0.35 l/kg/h and that of its metabolites was much higher. The renal clearance was the same for all compounds measured, approximately equal to 0.1 l/kg/h. Currently recommended dosage schedules appear to be too high in certain cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Accordingly, the finding that, in humans, DCQ was readily detectable in plasma during the absorption phase of CQ pointed to an enzymatic system with a high capacity (Ducharme and Farinotti, 1996). The predicted nonrenal clearance value of 0.52 Ϯ 0.04 ml/min/kg estimated from the present HLM investigations is in agreement with the one obtained in vivo from normal subjects (0.63-1.02 ml/min/kg; Frisk-Holmberg et al, 1983;Gustafsson et al, 1983;Ette et al, 1989).…”
Section: Chloroquine N-desethylation By Cyp2c8 Cyp3a4 and Cyp2d6supporting
confidence: 87%
See 2 more Smart Citations
“…Accordingly, the finding that, in humans, DCQ was readily detectable in plasma during the absorption phase of CQ pointed to an enzymatic system with a high capacity (Ducharme and Farinotti, 1996). The predicted nonrenal clearance value of 0.52 Ϯ 0.04 ml/min/kg estimated from the present HLM investigations is in agreement with the one obtained in vivo from normal subjects (0.63-1.02 ml/min/kg; Frisk-Holmberg et al, 1983;Gustafsson et al, 1983;Ette et al, 1989).…”
Section: Chloroquine N-desethylation By Cyp2c8 Cyp3a4 and Cyp2d6supporting
confidence: 87%
“…DCQ is rapidly detected in blood or plasma, its concentrations amounting to 20 to 50% of those of the parent Frisk-Holmberg et al, 1984). For BDCQ, plasma or blood concentrations never reach more than 10 to 15% of CQ levels (Frisk-Holmberg et al, 1983, 1984Augustjins et al, 1992). Although CQ possesses cytochrome P450 (P450)-inhibiting properties, notably on CYP2D6 (Lancaster et al, 1990;Halliday et al, 1995;Masimirembwa et al, 1995), the enzymes catalyzing its N-dealkylation have never been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroquine pharmacokinetics in patients with rheumatoid disease are reported to be similar to those in healthy volunteers (Augustijns et al 1992;Frisk-Holmberg et al 1983). The correlation between dosage and steady-state chloroquine concentration is reported to be very poor, reflecting the wide interpatient variation in pharmacokinetic parameters (Augustijns et al 1992;Frisk-Holmberg et al 1979;Laaksonen et al 1975).…”
Section: Disposition In Patients With Rheumatic Diseasesmentioning
confidence: 85%
“…[42, 43) Distribution and redistribution processes (from the various body compartments back to the intravascular space) rather than slow drug elimination, are the predominant factors governing chloroquine blood concentrations for months following its single dose administration,l20,44) Indeed, despite its long halflife, ranging from 20 to 60 days, chloroquine has a relatively high total clearance, approximating 0.10 Lih/kg from whole blood data and 0.7 to 1 L/h/kg from plasma data.l 8 ,20,21,42) In patients treated for long term arthritis, [45,46) or following multiple weekly doses for malaria prophylaxis, [22) the total plasma clearance of chloroquine was estimated at 0.35 to 1 Lih/kg.…”
Section: Eliminationmentioning
confidence: 98%